2021
DOI: 10.1002/psp.2435
|View full text |Cite
|
Sign up to set email alerts
|

Transnational divorce in binational marriages: The case of Portuguese–Brazilian and Portuguese–Cape Verdean couples

Abstract: While academic research has focused on binational marriages (i.e., marriages between partners of different national origins), transnational divorce is still under-researched in the field of migration and family studies. Drawing on qualitative data, this paper analyses the testimonies of Brazilian and Cape Verdean migrant women concerning their experiences of marriage and divorce from Portuguese partners. We adopt an intersectional approach to highlight how some central categories-gender, social class and migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
10
0
4
Order By: Relevance
“…Nonetheless, it is interesting to note that intersecting categories produce not only inequalities but also advantages, notably when the legal conflict occurs in the migrant partner's country of origin where his or her nationality provides certain rights despite his or her limited economic resources. This observation highlights the effectiveness of an intersectionality approach in uncovering not only migrant women's subordination but also their position of power in some contexts (see Gaspar, Ramos, & Fereira, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…Nonetheless, it is interesting to note that intersecting categories produce not only inequalities but also advantages, notably when the legal conflict occurs in the migrant partner's country of origin where his or her nationality provides certain rights despite his or her limited economic resources. This observation highlights the effectiveness of an intersectionality approach in uncovering not only migrant women's subordination but also their position of power in some contexts (see Gaspar, Ramos, & Fereira, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, it is evident that most studies focus on one specific social space of migrants, and often overlook the transnational dimension of their lives. In line with Al-Sharmani (2017), Urbańska (2016) and the articles in this Special Issue (Fresnoza-Flot, 2017;Gaspar et al, 2021;Qureshi, 2020;Sportel, 2021), this study analyses migrants' ability to negotiate with different issues and norms and to rely simultaneously on resources located in different countries. To gain deeper understanding of the link between migration and divorce, it adopts a global view on the process of migration by including the period before and after migration in the analysis.…”
Section: Migration and The Issue Of Divorcementioning
confidence: 95%
“…In France, Lévy (2020, p. 9) observed that some Chinese divorced women decided to marry a French man to regularise their migration situation due to their undocumented The contributions also unveil the precarious position of migrants in family law. For example, in Gaspar et al (2021) contribution, Brazilian and Cape-Verdean migrant women in problematic marriages may not automatically opt for divorce due to their unstable migration status linked to the absence of Portuguese citizenship. Once divorced, these women may be locked inside the country due to the prioritisation of child custody and visiting rights of the citizen father.…”
Section: The Impact Of Migration and Family Lawsmentioning
confidence: 99%
“…Five empirical research‐based papers comprise the present special issue, and all of them adopt qualitative data‐gathering methods. These contributions examine the experiences of transnational couples and involve migrants from Asia (Fresnoza‐Flot, 2021; Lévy, 2022; and Qureshi, 2020), Africa (Sportel, 2021; see also Gaspar et al, 2021), and Latin America (Gaspar et al, 2021). They engage in meaningful dialogue with one another by bringing to the fore the dominant elements and forces that shape the lives of the separating or divorced couples in their transnational social spaces: social and legal norms, social networks of support, and categories of difference.…”
Section: The Special Issuementioning
confidence: 99%
See 1 more Smart Citation